MiR-29a-3p Improves Acute Lung Injury by Reducing Alveolar Epithelial Cell PANoptosis - Cui, Yanhui; Wang, Xueqin; Lin, Fengyu; Li, Wen; Zhao, Yuhao; Zhu, Fei; Yang, Hang; Rao, Mingjun; li, Yi; Liang, Huaying; Dai, Minhui; Liu, Ben; et al. (Aging and disease, 2022)
Alveolar epithelial cell damage is an important determinant of the severity of acute lung injury/acute respiratory distress syndrome (ALI/ARDS). However, the molecular mechanisms of alveolar epithelial death during the development of ALI/ARDS remain unclear. In this study, we explore the role of miR-29a-3p in ALI/ARDS and its molecular mechanism. Plasma samples were collected from healthy controls and ARDS patients. Mice were intratracheally instilled with lipopolysaccharide (LPS) to establish acute lung injury. N6-adenosine (m6A) quantification, RNA-binding protein immunoprecipitation, cell viability assay, quantitative real-time polymerase chain reaction, and western blotting were performed. We found that miR-29a-3p was down-regulated in plasma of ARDS patients and lung tissue of ALI model mice, and miR-29a-3p agomir injection down-regulated the levels of the inflammatory factors, including tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) in the lungs, reducing alveolar epithelial cell PANoptosis as evaluated by the downregulation of Z-DNA binding protein 1 (ZBP1), gasdermin D (GSDMD), caspase-3, caspase-8, and mixed lineage kinase domain-like protein (MLKL), ultimately improving lung injury in the ALI model mice. Mechanism studies demonstrated that the knockout of methyltransferase 3 (N6-adenosine-methyltransferase complex catalytic subunit) removed the m6A modification of miR-29a-3p and reduced miR-29a-3p expression. Our findings suggest that miR-29a-3p is a potential target that can be manipulated for ALI/ARDS.